CT and MRI features of Primary Orbital Lymphoma: review of 14 cases - Jin, Chen Wang; Rana, Netra; Wang, Yuan; Ma, ShaoHui; Li, Min; Zhang, Ming (Asian Journal of Medical Sciences, 2011)
Objective: To assess the computed tomography (CT) imaging and magnetic resonance imaging (MRI) features of primary orbital lymphoma and to establish a differential diagnosis. Material & Methods: Fourteen patients (9 male and 5 female) suffering from primary orbital lymphoma underwent CT scanning with and without contrast. Pre- and post-contrast MRI scans were performed in 10 patients. Their ages ranged from 1.5 to 65 years (average age: 36 years). The course of diseases varied from 2 months to 16 years. Results: The diagnosis was confirmed pathologically in all cases. Lesions were bilateral in 4 cases and unilateral in 10 cases. Periorbital preseptal tissues were involved mainly in the upper lateral quadrant of the orbit. Focal masses were observed in 5 patients. Lesions that infiltrated the lacrimal gland, adjacent extraocular muscles and intraorbital tissues, along with the extraocular muscles, were found in other patients. The tumors that had advanced into intraorbital tissues and had involved extraocular muscles, displayed either a 'casting sign' or a 'ring sign'. Isodense soft-tissue masses with clear demarcation were found on plain CT film and lesions displayed low to intermediate signal intensity on T1- weighted MRI and relatively low or high signal intensity on T2-weighted MRI. The lesions demonstrated homogeneously marked enhancement on CT and MRI with contrast medium. Conclusion: CT imaging and MRI - particularly MRI - can demonstrate the location, configuration, inner structure and characteristic manifestations of the orbital lymphomas. This may assist the pre-operative diagnosis of these lesions. Key Words: Orbital tumor; Lymphoma; Pseudotumor; Computed tomography; Magnetic resonance imaging DOI: 10.3126/ajms.v1i2.3401 Asian Journal of Medical Sciences 1 (2010) 87-90